Pengaruh Inovasi Produk dan Selebriti Endorser terhadap Niat Beli Ulang Sepeda Motor Otomatis Honda - Rezkianto Akbar (BISMA (Bisnis dan Manajemen), 2018)
Honda Automatic motorcycle is best-selling Automatic motorcycle in Indonesia, in September 2014 - February 2015 Honda Automatic motorcycle sales declined notably Honda Vario Series amounted to 24.8%, and at the end of January 2015 Honda launched its newest Honda Automatic motorcycle Vario 150 ESP with various innovations performed, as well as using VJ Daniel Mananta as a celebrity endorser for communicating the latest product. This study are to analyze and discuss the influence of product innovation and celebrity endorser to re-purchase intention of Honda Automatic motorcycle. Based on the results of the t test is known that a product innovation has significant effect, while celebrity endorser has no significant effect on purchase intentions on Honda Automatic motorcycle. The contribution of product innovation and celebrity endorsers to the re-purchase intention of Honda Automatic motorcycle is 21.4%, while the rest influenced by other variables that are not used in this study.